2018
DOI: 10.1186/s12888-018-1681-3
|View full text |Cite
|
Sign up to set email alerts
|

Using photo-elicitation to understand reasons for repeated self-harm: a qualitative study

Abstract: BackgroundReasons for self-harm are not well understood. One of the reasons for this is that first-hand accounts are usually elicited using traditional interview and questionnaire methods. This study aims to explore the acceptability of using an approach (photo-elicitation) that does not rely on solely verbal or written techniques, and to make a preliminary assessment of whether people can usefully employ images to support a discussion about the reasons why they self-harm.MethodInterviews with eight participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 49 publications
(62 reference statements)
2
40
0
1
Order By: Relevance
“…All studies except Edmondson, Brennan, and House () reported that PP enabled varying degrees of mental and emotional processing. This section is divided into three sub‐themes: critical reflection, meaning‐making and narrative reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…All studies except Edmondson, Brennan, and House () reported that PP enabled varying degrees of mental and emotional processing. This section is divided into three sub‐themes: critical reflection, meaning‐making and narrative reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Despite being considered a novel approach (Edmondson, Brennan, and House 2018;Pini et al 2019), the method of PG photo-elicitation has developed in parallel with its RG counterpart (Dennis et al 2009), and intensified when cheap, simple point-and-press cameras could be given to participants (Rose 2012). However, researchers should still be aware that some individuals may not be able to produce photographs unassisted for instance because technology is not available (Samuels 2004) or due to physical incapacity (Radley and Taylor 2003).…”
Section: Photo-elicitationmentioning
confidence: 99%
“…This can happen for many reasons, such as difficulty with the concept of 311 capturing elements of their experiences visually (Drew et al, 2010) or practical 312 difficulties in capturing certain images (Edmondson, 2013). Researchers can respond 313 by developing an interview guide featuring a discussion of the practical and emotional 314 difficulties the participant has encountered in trying to capture images and what might 315 be missing from the photographs they present (Edmondson et al, 2018, Edmondson, 316 2013. 317 318…”
Section: Analytical Difficulties: 266mentioning
confidence: 99%
“…154and many studies have also found using photographs to explore meanings and 155 memories as a cathartic, positive, rewarding experience for participants(Balmer et al, 156 2015, Edmondson et al, 2018.157 158 Facilitating expression of meaningful data 159 The inclusion of photographs facilitates extensive and holistic accounts of participant 160 experience (Balmer et al, 2015). The photograph can take the researcher into 161 different environments (place of work, home, bedroom, hospital), with different 162 people (family, friends, colleagues) and add an emotional layer, which may be 163 difficult to verbalise (Balmer et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation